Duloxetine for prevention and treatment of chemotherapy-induced peripheral neuropathy (CIPN): systematic review and meta-analysis. Issue 1 (8th September 2022) - Chow, Ronald; Novosel, Madison; So, Olivia W; Bellampalli, Shreya; Xiang, Jenny; Boldt, Gabriel; Winquist, Eric; Lock, Michael; Lustberg, Maryam; Prsic, Elizabeth
Abstract : Introduction: Duloxetine has previously been reported to be promising in the setting of chemotherapy-induced peripheral neuropathy (CIPN). The aim of this study was to conduct a comprehensive systematic review and meta-analysis, on the use of duloxetine in prevention and treatment of CIPN. Methods: PubMed, Embase and Cochrane CENTRAL were searched from database inception up until April 2022. Articles were included in this review if they reported on duloxetine use in the setting of CIPN, in a multiarm comparative human trial. A random effects DerSimonian-Laird model was used to calculate summary risk ratios (RR) and corresponding 95% CIs, comparing duloxetine to placebo. This review was registered on. Results: Seven randomised controlled trials that included 645 patients were identified. Five reported on duloxetine for treatment of CIPN, and two for prevention of CIPN. Two studies had some concern for bias. Duloxetine was statistically similar to placebo in its efficacy, both in the treatment (RR 0.92, 95% CI 0.84 to 1.01) and prevention (RR 1.02, 95% CI 0.87 to 1.19) of CIPN. Safety profile was similar, in the treatment (RR 1.31, 95% CI 0.90 to 1.89) and prevention (RR 1.52, 95% CI 0.98 to 2.38) setting. Conclusion: There is currently limited evidence supporting duloxetine's use for CIPN. There is a need for more comprehensive and higher-quality trials assessing duloxetine in the setting of CIPN, before further clinical practice recommendations. Trial registration number: PROSPERO (CRD42022327487).